Answer:
![(x-43.45)(x+7.45)=0](https://tex.z-dn.net/?f=%28x-43.45%29%28x%2B7.45%29%3D0)
Step-by-step explanation:
We have the quadratic equation
i.e. ![d^{2}-36d-324=0](https://tex.z-dn.net/?f=d%5E%7B2%7D-36d-324%3D0)
As, the roots of the quadratic equation
are given by
.
So, from the given equation, we have,
a = 1, b = -36 , c = -324.
Substituting the values in
, we get,
![x=\frac{36\pm \sqrt{(-36)^{2}-4\times 1\times (-324)}}{2\times 1}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B36%5Cpm%20%5Csqrt%7B%28-36%29%5E%7B2%7D-4%5Ctimes%201%5Ctimes%20%28-324%29%7D%7D%7B2%5Ctimes%201%7D)
i.e. ![x=\frac{36\pm \sqrt{1296+1296}}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B36%5Cpm%20%5Csqrt%7B1296%2B1296%7D%7D%7B2%7D)
i.e. ![x=\frac{36\pm \sqrt{2592}}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B36%5Cpm%20%5Csqrt%7B2592%7D%7D%7B2%7D)
i.e. ![x=\frac{36\pm 50.9}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B36%5Cpm%2050.9%7D%7B2%7D)
i.e.
and ![x=\frac{36-50.9}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B36-50.9%7D%7B2%7D)
i.e.
and ![x=\frac{-14.9}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-14.9%7D%7B2%7D)
i.e. x = 43.45 and x = -7.45
Thus, the roots of the equation are 43.45 and -7.45.
Hence, the factored form of the given expression will be ![(x-43.45)(x+7.45)=0](https://tex.z-dn.net/?f=%28x-43.45%29%28x%2B7.45%29%3D0)
Answer:
TRUE
Step-by-step explanation:
HOPE THIS HELPED!!
Plug the x value which is 2 back to the x and solve.
I gave you two answers because I wasn’t sure if the question was (x^2) - 2 or x^2-2.
Those two functions look similar but is totally different so keep that in mind.
Hope you have a victorious day!
Answer:
x = 4/15 and x= 10/3
Step-by-step explanation:
|9x-7|=|6x+3|
There are two solutions, one positive and one negative.
(9x-7)=6x+3 - (9x-7)=6x+3
We will take the positive one first
(9x-7)=6x+3
Subtract 6x from each side
(9x-6x-7)=6x-6x+3
3x -7=3
Add 7 to each side
3x-7+7 = 3+7
3x = 10
Divide by 3x/3 = 10/3
x = 10/3
Now we will take the negative solution
- (9x-7)=6x+3
Distribute the negative sign
-9x+7 = 6x+3
Add 9x to each side
-9x+9x+7 = 6x+9x+3
7 = 15x+3
Subtract 3 from each side
7-3 = 15x +3-3
4 = 15x
Divide by 15 on each side
4/15 =15x/15
4/15 =x
If you need clarification just reply back so I can help